Assessment of Diagnostic Performance of Quantitative Flow Measurements in Normal Subjects and Patients With Angiographically Documented Coronary Artery Disease by Means of Nitrogen-13 Ammonia and Positron Emission Tomography - Muzik, Otto; Duvernoy, Claire; Beanlands, Rob S.B.; Sawada, Steve; Dayanikli, Firat; Wolfe, Edwin R.; Schwaiger, Markus (Journal of the American College of Cardiology, 1998)
Objectives. Regional myocardial blood flow (MBF) and flow reserve measurements using nitrogen-13 (N-13) ammonia positron emission tomography (PET) were compared with quantitative coronary angiography to determine their utility in the detection of significant coronary artery disease (CAD). Background. Dynamic PET protocols using N-13 ammonia allow regional quantification of MBF and flow reserve. To establish the diagnostic performance of this method, the sensitivity and specificity must be known for varying decision thresholds. Methods. MBF and flow reserve for three coronary territories were determined in 20 normal subjects and 31 patients with angiographically documented CAD by means of dynamic PET and a three-compartment model for N-13 ammonia kinetics. Ten normal subjects defined the normal mean and SD of MBF and flow reserve, and 10 normal subjects were compared with patients. PET flow obtained in the territory with the most severe stenosis in each patient was correlated with the angiographic assessment of the stenosis (severity ≥50%, ≥70%, ≥90%). Receiver operating characteristic (ROC) curve analysis was performed for 1.5, 2.0, 2.5, 3.0 and 4.0 SD of flow abnormalities. Results. MBF and flow reserve values from the normal subjects and from territories with documented stenoses ≥50% were significantly different (p < 0.05). A significant difference was found between normal subjects and angiographically normal territories of patients with CAD. High diagnostic accuracy and sensitivity, with moderately high specificity, were demonstrated for detection of all stenoses. Conclusions. Quantification of myocardial perfusion using dynamic PET and N-13 ammonia provides a high performance level for the detection and localization of CAD. The specificity of dynamic PET was excellent in patients with a low likelihood of CAD, whereas an abnormal flow reserve in angiographically normal territories was postulated to represent early functional abnormalities of vascular reactivity.